Refleksi implementasi kurikulum merdeka dalam perspektif pendidikan berkeadilan - Riswanto, Riswanto (Universitas Negeri Yogyakarta, 2025)
The independent curriculum is an improved curriculum from the emergency curriculum implemented during the Covid 19 pandemic. This curriculum replaces the 2013 curriculum with several improvements to overcome deficiencies and the effects of learning loss. The principle of developing an independent curriculum refers to equal distribution of access and quality of education to provide equitable education. Therefore, it is necessary to study the relevance of policy in implementing independent policies towards equitable education. The aim of this research is to analyze the policies and policies of the independent curriculum in basic education and their relationship to the concept of equitable education. The method used in this research is a qualitative method, using a Systematic Literature Review (SLR) approach. In this method, article screening is done with the help of the Publish or Perish application. The results of the research are, it was found that the policies in the independent learning curriculum at the basic education level, viewed from the mandate of the National Education System Law and the perspective of critical pedagogy theory, have relevance and enthusiasm for realizing equitable education, for example inclusive education policies, learning Differentiation, digitalization of education, but many policies are still fragmented, causing a lack of consistency in realizing equitable education. Kurikulum merdeka merupakan penyempurnaan dari kurikulum darurat yang diberlakukan selama pandemi Covid 19, kurikulum ini menggantikan kurikulum 2013 dengan beberapa penyempurnaan untuk mengatasi kekurangan dan efek learning loss. Prinsip pengembangan kurikulum merdeka merujuk pada pemerataan akses dan mutu pendidikan agar dapat menghadirkan pendidikan berkeadilan. Oleh karena itu perlu dikaji relevansi kebijakan dalam penerapan kurikulum merdeka terhadap pendidikan berkeadilan. Tujuan penelitian ini adalah untuk menganalisis kebijakan dan penerapan kurikulum merdeka di pendidikan dasar dan keterkaitannya dengan konsep pendidikan berkeadilan. Metode yang digunakan dalam penelitian ini adalah metode kualitatif, menggunakan pendekatan Systematic Literatur Review (SLR). Dalam metode ini Screening artikel di lakukan dengan berbantukan aplikasi Publish or Perish. Hasil dari penelitian ini ditemukan bahwa kebijakan-kebijakan dalam kurikulum merdeka belajar di tingkat pendidikan dasar, ditinjau dari amanat Undang-Undang Sistem Pendidikan Nasional dan perspektif teori pedagogi kritis, memiliki relevansi dan semangat untuk mewujudkan pendidikan berkeadilan, misalnya kebijakan pendidikan inklusif, pembelajaran berdefferensiasi, digitalisasi pendidikan, akan tetapi kebijakan-kebijakan masih banyak yang terfragmentasi sehingga menyebabkan kurang konsisten dalam mewujudkan pendidikan berkeadilan.